Preserving Tradition and Harmony: Customary Law’s Role in Resolving Ulayat Land Disputes - Rahakbauw, Leni Sipra Helen (Jurnal Ilmu Hukum Kyadiren, 2023)
In Indonesia, Indigenous Law Communities, exemplified by West Biak District, Papua, rely on customary law for conflict resolution in their territories. This research aims to address the resolution of ulayat land disputes and the optimization of the existence of customary law in the resolution of ulayat land disputes in West Biak District, Biak Numfor Regency. This qualitative study in West Biak District examines customary law’s role in cultural preservation and land dispute resolution. Primary data from interviews, secondary data from documents and literature, both analyzed for insights. The study reveals that customary land disputes in West Biak District result from unclear boundaries, unfair practices, the absence of historical witnesses, and increased land value. These are resolved via non-litigious mediation led by the traditional head, offering advantages over litigation